1970
DOI: 10.1113/jphysiol.1970.sp009045
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of functional vasodilatation in rabbit epigastric adipose tissue

Abstract: 1. The effect of close‐arterial infusions of fat‐mobilizing substances has been examined on the release of free fatty acids and blood flow in the epigastric adipose tissue of rabbits. 2. All the fat mobilizers in addition to causing the release of free fatty acids also caused an increased blood flow in the fat tissue. 3. Both the fat mobilization and the vasodilatation continued for an hour or so after the end of infusion. 4. Although no vasodilator substance could be detected in the venous effluent from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1970
1970
1983
1983

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This proposal is consistent with our observation that PGI 2 is produced in larger quantity than PGE 2 during NE-induced lipolysis, with the fact that PGI 2 is a more potent vasodilator than PGE 2 , and with the observation that no vasodilator substance could be detected in the venous effluent of the activated adipose tissue, but only from extracts of adipose tissue. 21 The last observation is consistent with the known instability of PGI 2 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This proposal is consistent with our observation that PGI 2 is produced in larger quantity than PGE 2 during NE-induced lipolysis, with the fact that PGI 2 is a more potent vasodilator than PGE 2 , and with the observation that no vasodilator substance could be detected in the venous effluent of the activated adipose tissue, but only from extracts of adipose tissue. 21 The last observation is consistent with the known instability of PGI 2 .…”
Section: Discussionsupporting
confidence: 89%
“…21 " 23 When lipolytic substances are infused into the arterial supply of adipose tissue, they also cause an increase in the blood flow to the adipose tissue. 21 This functional dilatation is abolished by indomethacin and aspirin. 23 Although it has been proposed that the vasodilator substance is PGE 2 , 22 ' 23 we suggest that it is PGI 2 .…”
Section: Discussionmentioning
confidence: 98%
“…In an earlier paper we showed that activation of rabbit adipose tissue by close arterial injection of lipolytic hormones resembles that in endocrine glands in being prolonged and accompanied by a prolonged increase in blood flow (Lewis & Matthews, 1968). More recently we were able to show that the functional vasodilatation in adipose tissue is accompanied by the release or formation of a vasodilator substance (Lewis & Matthews, 1970). In the present experiments we have examined the nature of the substance.…”
Section: Introductionmentioning
confidence: 96%
“…Lipolytic agents were infused close-arterially to the epigastric adipose tissue as described earlier (Lewis & Matthews, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Prostaglandin formation has been demonstrated in adipose tissue following nervous or hormonal stimulation (Shaw & Ramwell, 1968;Lewis & Matthews, 1970). The prostaglandin release associated with the vasodilatation accompanying lipolysis in rabbit was found to be prevented not only by prostaglandin synthetase inhibitors (Bowery & Lewis, 1973) but also by glucocorticoids (Lewis & Piper, 1975).…”
Section: Introductionmentioning
confidence: 99%